1993
DOI: 10.1111/j.1600-0897.1993.tb00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of the Secretory IgA (sIgA) System: Estradiol‐ and Progesterone‐induced Changes in sIgA in Parotid Saliva Along the Menstrual Cycle

Abstract: The effect of estradiol (E2) and progesterone (P4) on the IgA system, both at the systemic and at the mucosal level, was studied in 10 healthy young adult Mexican women during two consecutive menstrual cycles (MC); the control group consisted of five young adult Mexican men. Eight matched samples of blood and parotid saliva were obtained, in which serum E2, P4, and IgA were quantified. Parotid saliva was obtained with Curby's device and sIgA was quantified by an ELISA method. The MC was divided into follicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…These findings have been supported by others using different vaccines in humans and nonhuman primates (29,30,37,50). The results of the present study extend our understanding of mucosal sites for administration of nonreplicating vaccines in humans by showing that either N imm or R imm can be effective for induction of mucosal IgA Ab responses in the rectum.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These findings have been supported by others using different vaccines in humans and nonhuman primates (29,30,37,50). The results of the present study extend our understanding of mucosal sites for administration of nonreplicating vaccines in humans by showing that either N imm or R imm can be effective for induction of mucosal IgA Ab responses in the rectum.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, Ig concentrations in sera, saliva, or rectal secretions of women or nonhuman primates are not dramatically influenced by the menstrual cycle (36,37). These findings were confirmed in this study by comparing the IgA1, IgA2, IgG, and IgM concentrations measured by ELISA in sera and undiluted secretions collected from all women during either the midfollicular or midluteal menstrual cycle phases (all comparisons p Ͼ 0.05 by ANOVA).…”
Section: Ig Concentrations In Sera and Undiluted Secretionssupporting
confidence: 75%
“…Previous studies have shown that secretion of proteins and the inorganic components of saliva is hormone-related (Tenovuo et al 1981, Gómez et al 1993, Salvolini et al 1998, Laine & Pienihäkkinen 2000 and HRT appears to increase saliva flow rate, buffer effect and protein content of saliva in menopausal women (Laine & Leimola-Virtanen 1996, Leimola-Virtanen et al 1997, Eliasson et al 2003. In our present study, we identified ER in both mucous and serous acinar and ductal cells in minor salivary glands, and in parotid and submandibular glands.…”
Section: Discussionsupporting
confidence: 59%
“…During the menstrual cycle, specific changes can be observed in saliva composition, e.g. in the levels of salivary peroxidase (Tenovuo et al 1981) and secretory IgA (Gómez et al 1993). Similarly, the inorganic and protein composition of saliva changes during the course of pregnancy (Salvolini et al 1998), and in late pregnancy the salivary buffer effect is significantly decreased (Laine & Pienihäkkinen 2000).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Serum IgA shows slight fluctuations with changes in serum level of oestradiol; the level of secretory IgA in parotid saliva is significantly higher in the follicular phase than in the luteal phase, and higher in women than in men. 23 In rats, the IgA, IgG and SC levels significantly decrease in cervical vaginal secretions of ovariectomized rats treated with either oestradiol or progesterone. 24 Our previous study showed that, in mice, transport of polymer IgA into the male genital tract greatly increased following orchiectomy.…”
Section: Introductionmentioning
confidence: 99%